FEATURES OF THE TREATMENT OF HYPERMOBILITY OF THE ARTICULAR HEADS AND DISLOCATIONS OF THE LOWER JAW ON THE BACKGROUND OF FRACTURES OF THE CONDYGAL PROCESSES OF THE MANDIBLE, AS A PREVENTION OF ALLOPLASTIC REPLACEMENTS OF THE TEMPOMANDIBULAR JOINT - O.A. Toropov; D.S. Avetikov; M.G. Skikevych; O.S. Ivanytska; O.O. Rozkolupa; K.P. Lokes (Український стоматологічний альманах, 2024)
Acute, chronic, and recurrent dislocations are currently defined as conditions in which the mandibular process becomes dislocated from its joints and requires manipulation by another person to return to its normal position. Such conditions are usually preceded by either iatrogenic factors, including fractures of the mandibular branch, or joint instability and hypermobility of its heads. This pathology requires a personalized treatment algorithm: in each case, the clinical and radiological signs of this pathology should be clearly taken into account and the method of conservative or surgical treatment should be determined. Each of them has its advantages and disadvantages, and their combined use is also possible, which is the key to preventing more significant complications that can lead to allostatic replacements, joint components, or joint replacement as a whole.